Adults’ leisure-time physical activity preferences and association with physical activity guidelines by metropolitan status, United States, 2019 - Christiaan G. Abildso; Eugene C. Fitzhugh; Alan M. Beck; Ashleigh Johnson; Dina L. Maruca; Stefanie M. Meyer; Cynthia K. Perry; Carissa R. Smock; Zachary Townsend; Lauren E. Jacobs; M. Renée Umstattd Meyer (PLoS ONE, 2026)
Background Rural US adults experience disparities in meeting the physical activity guidelines (PAGs). Little is known about preferred types of leisure-time physical activity (LTPA), nor their relationship with meeting the PAGs. This study aimed to identify the most prevalent LTPAs among US adults, the relationship between LTPA types and meeting PAGs, and how these differed by residential status. Methods 2019 Behavioral Risk Factor Surveillance Study data were analyzed. Age-adjusted prevalence of 75 LTPAs and 11 categories of LTPAs that respondents spent the “most time” and “next most time” in during the previous month were compared by residential status (metropolitan; non-metropolitan). Logistic and multinomial logistic regression analyses adjusted for a variety of factors were used to compare the prevalence of meeting aerobic-, muscle strengthening, and combined PAGs by residential status. Age-adjusted prevalence of meeting the combined PAGs by 11 LTPA categories was compared by metropolitan status. Results Walking was the most prevalent LTPA (44.1%). Lawn/garden, hunting/fishing, household, farm/ranch work, childcare, and winter activities were more prevalent among non-metropolitan (rural) residents. Walking, running/jogging, weightlifting, conditioning, other activities, sports, bicycling, water activities, and dance were more prevalent among metropolitan (urban) residents. Non-metropolitan residents were less likely to meet the minimal aerobic-, muscle-strengthening, and combined PAGs, and were more likely to be inactive. Among adults that engaged in walking, roughly 25% met the combined PAGs and about 22% did not meet either PAG. Conclusions When creating targeted rural PA interventions, LTPA preferences could be embraced and augmented or the non-preferred LTPAs could be adapted.